n+(90-n)=90solven

Simple and best practice solution for n+(90-n)=90solven equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+(90-n)=90solven equation:


Simplifying
n + (90 + -1n) = 90solven

Remove parenthesis around (90 + -1n)
n + 90 + -1n = 90solven

Reorder the terms:
90 + n + -1n = 90solven

Combine like terms: n + -1n = 0
90 + 0 = 90solven
90 = 90solven

Solving
90 = 90elnosv

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-90elnosv' to each side of the equation.
90 + -90elnosv = 90elnosv + -90elnosv

Combine like terms: 90elnosv + -90elnosv = 0
90 + -90elnosv = 0

Add '-90' to each side of the equation.
90 + -90 + -90elnosv = 0 + -90

Combine like terms: 90 + -90 = 0
0 + -90elnosv = 0 + -90
-90elnosv = 0 + -90

Combine like terms: 0 + -90 = -90
-90elnosv = -90

Divide each side by '-90lnosv'.
e = l-1n-1o-1s-1v-1

Simplifying
e = l-1n-1o-1s-1v-1

See similar equations:

| 40+4=4x-60 | | 3a+5+2a=45 | | 4y-3+2y-5=22 | | 8a(1a-2)=5(a+6) | | 8a(1a-2)=-5(a+6) | | 8a-7=2+9a | | 3x+7=0.5x+2 | | 2x-5=0.5x+4 | | 5x-2=0.5x+7 | | f(4)=6*x+3 | | (x-6)*5=2x | | x-6*5=2x | | 144=72+9x | | 7x-9-3(x-6)=2x | | 3x-2-9(x-6)=2x | | 3x-2-9(x-1)=2x | | 3x-2(x-1)=2x | | 6x(x+2)=5-x | | (7-2i)(3-5i)= | | 4z^2+6z+3=0 | | 3(4x-5)=11x+20 | | (x-4)(x-10)=-9 | | -5x^2=-7x+13 | | y^2-6y=-6 | | 2a^3-9a^2-17a-6=0 | | 3x-2(x+1)=2x | | -4x^2+16x=19 | | 3x-2=41.5 | | 4x^2-36x+79=0 | | 2r^2-5r=3 | | 3c^2-22c=16 | | -3-4x=-10 |

Equations solver categories